Jurnal Review Aktivitas Antidiabetes dan Kandungan Senyawa Kimia dari Berbagai Bagian Tanaman Alpukat (Persea americana) - Dani Sujana; Nurul Nurul; hasbi Taobah Ramdani (Jurnal Medika Cendikia, 2019)
Diabetes is a degenerative disease caused by unhealthy lifestyles in the case of type 2 diabetes. Hyperglycemia occurs due to endocrine disruption resulting in defective insulin secretion, insulin resistance or both. Avocado (Persea americana) has been known to have pharmacological activity, one of which is as an antidiabetic. Treatment using natural ingredients should be based on scientific evidence. This review journal was compiled from the online literature of local and international journals. Electronic search by keyword Persea americana, Plant Parts, Chemical Compounds and Antidiabetic Activity at several sites, such as NCBI, Elsevier and Pubmed. It is known that various parts of the Persea americana plant contain saponins, tannins, flavonoids, alkaloids, phenols and steroids. These compounds are responsible for various pharmacological activities that are caused.